The Role of Urban Geography in Supporting and Developing the Tobruk Free Zone: An Analytical Study in Urban and Economic Planning - Saeed AL-Dahia (AlQalam Journal of Medical and Applied Sciences, 2025)
The study explores the critical use of urban geography in the development and consolidation of Free Economic Zones (FEZs), with particular reference to Tobruk, Libya. The research identifies Tobruk’s advantageous geographical attributes, such as a natural deep harbour, closeness to the Egyptian border, and important transportation routes, while analyzing infrastructure weaknesses and urban planning matters. Through spatial analysis and urban planning evaluation, the study demonstrates how integral geographic and economic planning through the use of modern geospatial technologies can remake Tobbaar as a thriving economic hub. Recommendations are provided for improving infrastructure, making land-use planning rational, and promoting sustainable development.